2014
DOI: 10.1177/0042085914525791
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors in Mathematically Talented Black Male Students

Abstract: Within urban elementary schools are Black students who continue to challenge the normative deficit characterization of the educational opportunities of students like them. This study attempts to provide a more holistic picture of the scholarly trajectories of 13 African American males who are particularly talented in mathematics and who attended urban schools. PVEST to used to explore stage-specific outcomes to identify dynamic and situational risk and protective factors, both internal and external, by which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 48 publications
3
50
0
Order By: Relevance
“…Play serves as a catalyst for curiosity, initiative, investigation, innovation, and creativity (Alexander, Johnson, & Kelley, ). Further, play (e.g., puzzles, blocks, flashcards, video and internet games) facilitates knowledge development and interest in math and science (Maltese, Melki, & Wiebke, ; McGee & Perman, ; Strayhorn, ). For play to be an effective tool for learning, however, it needs to be incentivized, encouraged, and intentional.…”
Section: Literaturementioning
confidence: 99%
“…Play serves as a catalyst for curiosity, initiative, investigation, innovation, and creativity (Alexander, Johnson, & Kelley, ). Further, play (e.g., puzzles, blocks, flashcards, video and internet games) facilitates knowledge development and interest in math and science (Maltese, Melki, & Wiebke, ; McGee & Perman, ; Strayhorn, ). For play to be an effective tool for learning, however, it needs to be incentivized, encouraged, and intentional.…”
Section: Literaturementioning
confidence: 99%
“…Traditional theorizing frequently excludes any examination of the myriad structural and institutional barriers that impede Black parents' and students' ability to successfully navigate STEM fields. This study adds to the recent research in STEM education that pushes back against deficit perspectives of Black parental support, instead showcasing these parents' talents in circumnavigating racialized educational paradigms (Berry, Thunder, & McClain, 2011;Martin, 2006, McGee & Pearman, 2014Mickelson et al, 2011;Noble & Morton, 2013).…”
mentioning
confidence: 84%
“…Additional research studies investigating the mathematics experiences of African American pre-service elementary education teachers, through the use of narrative analysis have exposed details on how Black parents help these student teachers learn, participate, and succeed in mathematics in their early years of schooling (McGee & Pearman, 2014). Ten of the 13 students in this study discussed early positive and beneficial mathematics learning experiences with their fathers or a close male relative (e.g., uncle, grandfather).…”
Section: Parental Influence On Children's Socialization Toward Mathemmentioning
confidence: 99%
“…His shooting and the acquittal of his murderer illustrate how institutional and structural racism still exists in the U.S. (Fulkerson, 2012). McGee (2014) reported that a highachieving Black male math student, refused to attend or even consider any college or university in Florida as a result of the "stand your ground" law. The Martin and Davis killings-just two of many-have highlighted and underscored the urgency of the condition of many young Black males, not only regarding education but also their basic right to life.…”
Section: Introductionmentioning
confidence: 99%